Birdpedia : a brief compendium of avian lore - Leahy, Christopher, 1945- (Princeton University Press, 2021)
"This book is an engaging and interesting compendium of bird facts. Presented in a format similar to that of Lawrence Millman's Fungipedia, the book contains alphabetized entries on all things birds- from basic biology, through taxonomy, to folklore and potted biographies of key figures in the development of ornithology. Entries are written with a general audience in mind, but are charming enough to attract expert birders as well. The book has roughly 180 entries, on topics such as "anting," where birds visit ant nests to allow ants to crawl over their plumage, a method of killing feather mites, to entries on famous ornithologists such as Alexander Wilson and John James Audubon. The entries will be accompanied by approximately 50 black and white line drawings by Abby, McBride"--